Exploring Nostalgia - Gandini, Alessandro (Taylor & Francis, 2026)
This volume provides an overview of a number of different areas of social and cultural life in which nostalgia is shown to be an important prism for understanding and analysing human thoughts, actions and feelings. Featuring a rich collection of empirical studies and analyses of nostalgia, the contributors demonstrate creative ways to study nostalgia – from qualitative methods such as in-depth interviews/narrative analyses to experimental methods that involve inducing nostalgia in research participants. Altogether, these studies highlight the variability of the experience of nostalgia as well as the usefulness of nostalgia at both individual and collective levels, ultimately showing nostalgia to be a helpful, enriching emotion in everyday, pragmatic ways and also at deep, philosophical levels. Exploring Nostalgia will appeal to scholars, academics, faculty and advanced students with interests in social theory, psychology, cultural studies and the sociology of emotions. Chapter 3 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.